Financial Strategy and Profitability Performance: Financial Ratio Analysis of the Telecommunications Industry on the Indonesia Stock Exchange - Mubarok, Faizul; Utami, Tutik Sri; Ishanifah, Annisa; Mawarni, Annisa Putri (Telaah Bisnis, 2024)
This quantitative analysis aims to provide empirical evidence regarding the impact of solvency, liquidity, activity, and company age on the level of profitability in telecommunications companies. The research sample consists of six companies in the telecommunications sector listed on the Indonesia Stock Exchange (IDX) during the 2018-2022 period. The data comes from each company's financial statements, accessed through the Indonesia Stock Exchange with the panel regression method. The results of this study indicate that liquidity and company age have a positive and significant influence on the profitability of telecommunications companies. In contrast, solvency and activity have no significant impact. These findings provide a better understanding of the factors that contribute to the profitability performance of companies in the sector. The practical implication of this study is that the management of telecommunication companies can focus more on strategies that increase the level of liquidity and consider the company's age in their financial policy planning. By understanding the impact of these variables, companies can optimize their financial structure to achieve better profitability levels. This research can serve as a foundation for better decision-making in managing the financial aspects of telecommunication companies.